Severe Acute Respiratory Syndrome Coronavirus nsp1 Protein Suppresses Host Gene Expression by Promoting Host mRNA Degradation - Kamitani, Wataru; Narayanan, Krishna; Huang, Cheng; Lokugamage, Kumari; Ikegami, Tetsuro; Ito, Naoto; Kubo, Hideyuki; Makino, Shinji (Proceedings of the National Academy of Sciences - PNAS, 2006)
Severe acute respiratory syndrome (SARS) coronavirus (SCoV) causes a recently emerged human disease associated with pneumonia. The 5' end two-thirds of the single-stranded positive-sense viral genomic RNA, gene 1, encodes 16 mature proteins. Expression of nspl, the most N-terminal gene 1 protein, prevented Sendai virus-induced endogenous IFN-β mRNA accumulation without inhibiting dimerization of IFN regulatory factor 3, a protein that is essential for activation of the IFN-β promoter. Furthermore, nspl expression promoted degradation of expressed RNA transcripts and host endogenous mRNAs, leading to a strong host protein synthesis inhibition. SCoV replication also promoted degradation of expressed RNA transcripts and host mRNAs, suggesting that nspl exerted its mRNA destabilization function in infected cells. In contrast to nspl-induced mRNA destablization, no degradation of the 285 and 18S rRNAs occurred in either nspl-expressing cells or SCoV-infected cells. These data suggested that, in infected cells, nspl promotes host mRNA degradation and thereby suppresses host gene expression, including proteins involved in host innate immune functions. SCoV nspl-mediated promotion of host mRNA degradation may play an important role in SCoV pathogenesis.